2022
DOI: 10.2340/17453674.2022.2430
|View full text |Cite
|
Sign up to set email alerts
|

Do changes in outcomes following primary and revision hip replacement differ and relate to markers of socioeconomic status? A 1-year population-based cohort study

Abstract: Background and purpose: There is little evidence on improvement after revision total hip replacement (THR). Moreover, improvements may be associated with socioeconomic status (SES). We investigated whether changes in Harris Hip Score (HHS) differ among patients undergoing primary and revision THR, and their association with markers of SES. Patients and methods: We conducted a populationbased cohort study on 16,932 patients undergoing primary and/or revision THR from 1995 to 2018 due to hip osteoarthritis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In a recent study examining the effects of socioeconomic status on Harris hip scores at 1 year after primary and revision THAs, Stisen et al observed improvement in patient-reported outcome scores at the 1-year follow-up 6 . Using a database of 16,932 patients undergoing a surgical procedure between 1995 and 2018, the authors found that scores were 2.6 points (95% CI, 2.1 to 3 points) higher for primary THA for patients with high wealth compared with those with low wealth and 12 points (95% CI, 10 to 14 points) higher for patients with high education compared with those with low education.…”
Section: Patient Factors In Relation To Outcomes Socioeconomicsmentioning
confidence: 99%
“…In a recent study examining the effects of socioeconomic status on Harris hip scores at 1 year after primary and revision THAs, Stisen et al observed improvement in patient-reported outcome scores at the 1-year follow-up 6 . Using a database of 16,932 patients undergoing a surgical procedure between 1995 and 2018, the authors found that scores were 2.6 points (95% CI, 2.1 to 3 points) higher for primary THA for patients with high wealth compared with those with low wealth and 12 points (95% CI, 10 to 14 points) higher for patients with high education compared with those with low education.…”
Section: Patient Factors In Relation To Outcomes Socioeconomicsmentioning
confidence: 99%
“…Revision THR is a technically more challenging procedure than primary THR; however, patients undergoing revision THR report improvements in pain and function (Saleh et al., 2003). Nevertheless, a registry‐based analysis demonstrated poorer clinical outcomes on hip pain and function for patients after revision THR than following primary THR (Stisen et al., 2022). Evidence on revision THR in terms of the effectiveness of pain relief and functional improvement is sparse (Singh & Lewallen, 2013), and no consensus exists on optimal rehabilitation after revision THR (Newman & Barker, 2017).…”
Section: Introductionmentioning
confidence: 99%